(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Deconstruction is a philosophy of change, of the unpredictable and the impredictable, of the new and the surprising. It does not work on the assumption that a poet’s writing is of a piece, innately given, the end of which is sketched out right in the beginning.Eliot, like Derrida, strikes at the root of dogmatism. As a result, their criticism is characterized the way they make reservations, qualify positive assertions and introduce parentheses. Eliot, at times, becomes critical of his own pronouncements by offering recantations. In the essay,’ To Criticise the Critic’, he turns against his youthful utterances. There are,he says, statements with which he no longer agrees there are views whichhe maintains with less firmness of conviction than when he first expressedthem, or which he maintains with imperfect reservations. Deconstruction infreeing the critic from dogmatism makes the critic humble. Derrida too, ishumble to the degree possible.